Application of a graded approach in regulating the safety of radiation sources. (IAEA-TECDOC, 2021)
"Provides practical information on the application of a graded approach in regulating the safety of radiation sources ... The methodologies described promote a systematic and consistent approach to regulation in accordance with IAEA Safety Standards"--Foreword.